How Social Media Promotion, Online Sales, And Developing Networks Influence Company Financial Performance - Eksanti Nishandini; Mutiara Khikmatul Maolidah; Nuril Khusni Al Amin (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research investigates the influence of social media promotion, online sales, and network development on company financial performance. The study aims to comprehend how these elements interact to shape financial outcomes. Employing a qualitative approach, the research utilizes in-depth interviews, case studies, and thematic analysis to explore the dynamics of social media promotion, online sales strategies, and network expansion. Sampling techniques involve purposive selection of participants from various industries to capture diverse perspectives. Findings reveal relationships between these components and financial performance, emphasizing the significance of strategic integration and effective management. The study contributes to a nuanced understanding of contemporary business dynamics, empowering companies to optimize their digital marketing strategies and network engagements for enhanced financial results.